THE STATE-EMBEDDED ORGANIZATIONAL BROKER: HOW COLLECTIVE ACTION DILEMMAS ARE RESOLVED IN NEIGHBORHOOD RENEWAL - Pengyu Ding (PEOPLE: International Journal of Social Sciences, 2026)
How does governance consensus emerge in high-distrust, high-heterogeneity urban neighborhoods where both routine bureaucratic mobilization and community self-organization fail? Through a Bayesian process-tracing analysis of one neighborhood renewal project in Shanghai—where 1,126 households reached 100% agreement within forty-nine days despite 97 distinct floor-plan configurations and entrenched state–society distrust—this study establishes that consensus formation depends on a two-phase organizational brokerage mechanism. In the prerequisite phase, structural embeddedness (M₁) provides the legitimacy platform without which no negotiation can begin. In the recursive coupling phase, information brokerage (M₂) and resource brokerage (M₃) operate concurrently in mutually reinforcing feedback: information translation creates the cognitive conditions for material proposals to be credibly evaluated, while iterative resource adjustments generate new informational content for diffusion. This study introduces the concept of the State-Embedded Organizational Broker (SEOB) and highlights political authorization as a critical brokerage resource that has received limited explicit attention in existing brokerage research. In doing so, it extends brokerage theory into a state-embedded governance context and provides a structured analytical approach for examining mechanism-based coordination in complex urban settings.